CRIMINAL LEXICON AND ITS REPRESENTATION (World Bulletin of Social Sciences, 2023)
Gang language/speech has a special place in the social lexicon. There are special words and expressions in the speech of the representatives of this world, and usually, in scientific sources, such tools are called slang, criminal slang, mafia language.